Chicken-Specific Kinome Analysis of Early Host Immune Signaling Pathways in the Cecum of Newly Hatched Chickens Infected With Salmonella enterica Serovar Enteritidis - Kogut, Michael H.; Genovese, Kenneth J.; Byrd, J. Allen; Swaggerty, Christina L.; He, Haiqi; Farnell, Yuhua; Arsenault, Ryan J. (Frontiers in Cellular and Infection Microbiology, 2022)
Poultry is a major source of human foodborne illness caused by broad host range Salmonella serovars (paratyphoid), and developing cost-effective, pre-harvest interventions to reduce these pathogens would be valuable to the industry and consumer. Host responses to infectious agents are often regulated through phosphorylation. However, proteomic mechanisms of Salmonella acute infection biology and host responses to the bacteria have been limited concentrating predominately on the genomic responses of the host to infection. Our recent development of chicken-specific peptide arrays for kinome analysis of host phosphorylation-based cellular signaling responses provided us with the opportunity to develop a more detailed understanding of the early (4-24 h post-infection) host-pathogen interactions during the initial colonization of the cecum by Salmonella. Using the chicken-specific kinomic immune peptide array, biological pathway analysis showed infection with S. Enteritidis increased signaling related to the innate immune response, relative to the non-infected control ceca. Notably, the acute innate immune signaling pathways were characterized by increased peptide phosphorylation (activation) of the Toll-like receptor and NOD-like receptor signaling pathways, the activation of the chemokine signaling pathway, and the activation of the apoptosis signaling pathways. In addition, Salmonella infection induced a dramatic alteration in the phosphorylation events of the JAK-STAT signaling pathway. Lastly, there is also significant activation of the T cell receptor signaling pathway demonstrating the initiation of the acquired immune response to Salmonella infection. Based on the individual phosphorylation events altered by the early Salmonella infection of the cecum, certain conclusions can be drawn: (1) Salmonella was recognized by both TLR and NOD receptors that initiated the innate immune response; (2) activation of the PPRs induced the production of chemokines CXCLi2 (IL-8) and cytokines IL-2, IL-6, IFN-α, and IFN-γ; (3) Salmonella infection targeted the JAK-STAT pathway as a means of evading the host response by targeting the dephosphorylation of JAK1 and TYK2 and STAT1,2,3,4, and 6; (4) apoptosis appears to be a host defense mechanism where the infection with Salmonella induced both the intrinsic and extrinsic apoptotic pathways; and (5) the T cell receptor signaling pathway activates the AP-1 and NF-κB transcription factor cascades, but not NFAT.